When Jack Blinks: Si(gh)ting gay desire in Ann Bannon's Beebo Brinker - Barale, Michèle Aina (Feminist studies, college park, 1992)
The overtly lesbian story, "Beebo Brinker," by Ann Bannon offers the heterosexual male reader an opportunity to engage in nonheterosexual imaginings. Bannon's story is examined for its subcultural appropriation and subversion as a crossover novel in reverse.
Keywords: approches et analyses; arts; discipline; hétérosexisme; identités LGBTQIA2+; lesbianisme; ressource en ligne; systèmes d'oppressions; études littéraires